Caracterização de filmes de nanopartículas de óxido de níquel - Mello, Thiago Ismael Torrano do Amaral (2020)
Nanomaterials have aroused interest in several areas of application due to properties, such as high surface area and quantum effects. Thin films of semiconductor oxides have applications in the area of optics, electronics and sensors. Nickel oxide nanoparticles have interesting properties for application as a gas sensor due to the semiconductor behavior of nickel oxide and the change in electrical response when in contact with oxidizing and reducing gases. With a high surface area, resulting from the nanometric size of the particle, the interactions of the material surface with the gas under analysis are intensified. One of the challenges involving its application is the deposition of particles with low agglomeration on substrates, to meet this need deposition techniques have been developed to improve the deposition of nanomaterials. In this work, nickel oxide nanoparticles were dispersed in toluene and deposited using the interfacial technique, which consists of arranging the material at the interface between two immiscible liquids on a substrate. A nickel oxide sample was synthesized to study the crystalline structure of the material, it was not used for deposition, but the synthesis showed the cubic crystalline structure with a centered face. The deposition occurred with concentrations of 0.5 and 1.0 mg / mL of nickel oxide in toluene, and the deposition of up to 5 layers of nickel oxide on the same substrate was studied. The thickness and roughness of the layers were obtained by profiling. Electron microscopy images of the deposited particles demonstrated that the technique forms homogeneous surfaces of the deposited material despite having the formation of agglomerates the greater the number of deposited layers. The greater the concentration, the greater the size of the clusters and the greater the number of layers, the greater the clusters. Roughness and thickness follow the same principle. The deposition technique is promising on the laboratory scale since it can uniformly deposit the entire surface of the substrate as well as distribute the material in ways that were not possible when done by casting or spin coating.